Sexual violence and hybrid peacebuilding: how does silence 'speak'?. Issue 4 (4th July 2017) - George, Nicole; Kent, Lia
Abstract: This paper reflects on the gendered impacts of hybrid peacebuilding processes in Timor-Leste and Bougainville. We consider the interplaying local and global influences that shape how women's stories of conflict-related sexual violence are received, and consider the silences that often shroud these experiences. In contradiction to the global push to expose sexual violence as part of peacebuilding efforts, we offer a more ethnographically focused examination of women's silences. Our analysis challenges mainstream accounts of the way silence 'speaks' to the shame of conflict-related sexual violence and has relevance to broader debates about hybrid approaches to conflict resolution.